Targeting Dopamine Transporter (DAT) with Peronema canescens Bioactives: A Molecular Docking Study for Stroke-Related Pain and Sedation Management - Rizki Rachmad Saputra; Rifaldi Lutfi Fahmi; Eka Novitasari; Luluil Maknun; Jeddah Yanti; Raiyan Fairozi (Helium: Journal of Science and Applied Chemistry, 2025)
Pain and drowsiness are common symptoms of stroke recovery, which can be difficult to manage owing to neurochemical abnormalities in the dopamine system. The Dopamine Transporter (DAT) controls dopamine levels, which influences pain perception and neurological recovery. This study examines bioactive chemicals found in Peronema canescens leaves and their possible interactions with DAT. AutoDock Vina was used to perform molecular docking simulations to determine the binding affinities of Peronemin derivatives (A2, A3, and B2) to the Dopamine Transporter (DAT). The receptor structure (PDB ID: 4M48) was created by eliminating water molecules, introducing polar hydrogens, and optimizing the structure using AutoDockTools. Ligand structures were translated to the proper format, and docking was conducted using a grid box centered on DAT's active site, with an exhaustiveness value of 10. The Peronemin derivatives A2, A3, and B2 demonstrated binding affinities stronger than nortriptyline, native ligand (−10.6, −10.5, and −10.3 kcal/mol, respectively) and binding similarities ranging from 72.2% to 94.4%. These findings suggest that Peronema canescens bioactives may be promising candidates for stroke-related pain and sedative control, warranting further experimental validation.